Diacylglycerol kinase-ζ regulates mTORC1 and lipogenic metabolism in cancer cells through SREBP-1 - Torres-Ayuso, P (Oncogenesis, 2015)
Diacylglycerol kinases (DGKs) transform diacylglycerol (DAG) into phosphatidic acid (PA), balancing the levels of these key metabolic and signaling lipids. We previously showed that PA derived from the DGKζ isoform promotes mammalian target of rapamycin complex 1 (mTORC1) activation. This function might be crucial for the growth and survival of cancer cells, especially for those resistant to the allosteric mTOR inhibitor rapamycin. How this positive function of DGKζ coordinates with DAG metabolism and signaling is unknown. In this study, we used a rapamycin-resistant colon cancer cell line as a model to address the role of DGKζ in tumor cells. We found that DGKζ predominated over other PA sources such as DGKα or phospholipase D to activate mTORC1, and that its activity was a component of the rapamycin-induced feedback loops. We show that the DGKζ DAG-consuming function is central to cell homeostasis, as DAG negatively regulates levels of the lipogenic transcription factor SREBP-1. Our findings suggest a model in which simultaneous regulation of DAG and PA levels by DGKζ is integrated with mTOR function to maintain tumor cell homeostasis; we provide new evidence of the crosstalk between mTOR and lipid metabolism that will be advantageous in the design of drug therapies.